How to Build Community Mutual Assistance Initiatives During the COVID-19 Pandemic? : Communication Analysis on the Jogo Tonggo Movement - Nafila, Ukhtika Zulfa; Agustin, Helfi (Indonesian Journal of Social Responsibility Review (IJSRR), 2022)
The Indonesian government implemented a quarantine policy at the beginning of the COVID-19 pandemic. The implementation of quarantine in the community while the prevention of transmission for those who have been infected is by imposing selfisolation. For people who are self-isolating at home, the Central Java regional government has a program called Jogo Tonggo. Concept of the Jogo Tonggo is the neighbors help to supply the needs of residents who are self-isolating. This study aims to analyze the process of communication and coordination of village officials in building public awareness of the implementation of the Jogo Tonggo program during self-isolation for the prevention of COVID-19. This study uses a descriptive qualitative method, located in Gumelem Kulon Village, RT 01 RW 03 in January-December 2021.The technique for determining research subjects is purposive sampling. Informants in this study amounted to 12 people. Collecting data through interviews and observation. We found that communicators socialize the Jogo Tonggo program in Gumelem Kulon Village RW 03 by sending messages through WhatsApp groups. The messages conveyed included an invitation to help neighbors who are self isolation, providing support and not isolating them, as well as recommendations to continue to obey health protocols. The media used to socialize the Jogo Tonggo program, namely whats app social media, posters and billboards are only provided at the village hall and oral communication. The recipients of the Jogo Tonggo message are all people in Gumelem Kulon Village, especially in RW 03. The impact that occurs after residents receive the message, residents are willing to help the daily needs of self isolation families. Barriers to implementing the Jogo Tonggo program are the lack of communication between families who are self isolation to the RT/RW and messages that are not followed bypreventive measures because there are still residents who do not comply with health protocols. Communication and coordination carried out in Gumelem Kulon Village is unfully optimal yet. The media used is not evenly distributed and is not updated regularly